Clinical outcomes associated with guideline-discordant management of asymptomatic bacteriuria and urinary tract infection in hospitalized patients with neurogenic bladder - Margaret A. Fitzpatrick; Marissa Wirth; Jimmy Nguyen; Katie J. Suda; Frances M. Weaver; Stephen Burns; Eileen Collins; Nasia Safdar; Ursula Patel; Charlesnika T. Evans (Antimicrobial Stewardship & Healthcare Epidemiology, 2022)
Abstract